The Influence of Community Satisfaction Index on Investment Realization at the Investment and One-Stop Integrated Services Agency of Manado City - Sri Indriani Sugawa; Vecky A.J. Masinambow; Een N. Walewangko (Journal Research of Social Science, Economics, and Management, 2025)
Investment realization serves as a critical indicator of regional economic development, particularly in emerging markets where efficient public services play a pivotal role in attracting both domestic and foreign investment. This research aims to analyze the influence of the Community Satisfaction Index (CSI) on investment realization at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Manado City. The CSI is measured through three sub-variables: Service Information, Service Process, and Service Quality Results, which are operationalized through nine indicators according to Minister of Administrative and Bureaucratic Reform Regulation No. 14 of 2017. This quantitative research uses multiple linear regression analysis with a sample of 100 business actors who have processed permits and reported investment realization in 2024. The sampling technique used is purposive sampling with predetermined criteria. The results indicate that Service Information and Service Process have significant positive effects on investment realization, while Service Quality Results do not show a significant effect. Simultaneously, all three variables significantly influence investment realization, with an adjusted R² value of 57.67%. The research also reveals that 79% of respondents are domestic investors (PMDN) and 21% are foreign investors (PMA), with trade and repair services dominating at 40%. These findings underscore the importance of information clarity and service process efficiency in encouraging investment growth in Manado City. The research provides practical implications for DPMPTSP to focus on improving service information systems and streamlining permit processes to create a more conducive investment climate.